The Secret Mirror : Literary Form and History in Tocqueville's "Recollections'' - Shiner, Larry E. (Cornell University Press, 2019)
Tocqueville opens the Recollections, his deeply ambivalent memoir of the failed 1848 Revolution in France, with an explicit denial of any literary intent or rhetorical appeal. Forced by illness into an unaccustomed state of leisure, Tocqueville claims to record his experiences solely for his own amusement, holding up a "secret mirror" through which he will be able to contemplate the past truthfully. In this innovative study, L.E. Shiner examines the Recollections as a test case of the relation between form and content in historical writing. Drawing on current literary theory and semiotics, Shiner offers a close reading which at once confirms the inevitably literary character of historical writing and demonstrates how rhetorical analysis of Tocqueville's writings deepens our understanding of his political thought. Using the methods of reader-response and rhetorical criticisms, among others, Shiner first analyzes the component genres and narrative structures of the Recollections, the recurring pictorial and thematic codes, and the various voices Tocqueville employs. He then confronts the issue of the truth of Tocqueville's treatment of 1848, in part by comparing it with other key texts on these same events-Marx's The Class Struggles in France and Flaubert's Sentimental Education. Finally, Shiner pursues questions of authorial style, tracing the use of some of the rhetorical devices discussed in the Recollections through Tocqueville's Democracy in America, The Old Regime and the French Revolution, and "A Fortnight in the Wilderness."